A Lycopolitan Forgery of John's Gospel - Askeland, Christian 1976- (2015)
The internet publication of a Coptic Gospel of John fragment demonstrated that both it and the related Gospel of Jesus' Wife fragment were modern creations. The Coptic John fragment was clearly copied from Herbert Thompson's 1924 publication of the Lycopolitan Qau codex, and shared the same hand, ink and writing instrument with the Gospel of Jesus' Wife fragment. The present discussion will first survey the extant Coptic tradition of John's Gospel, and second outline the evidence for dependence on the Qau codex publication.
Keywords: Coptic; Gospel of Jesus' Wife; Forgery